Perbedaan Sensitivitas Antibiotik Pada Isolat Ulkus Akut dan Ulkus Kronik Pasien Diabetes Melitus Di RSUD Kraton Kabupaten Pekalongan - Mulia Susanti; Puspa Dewi (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Diabetes is a disease characterized by increased blood sugar levels, caused by pancreatic damage or insulin resistance or both. Various serious complications can occur of patient diabetes mellitus  one of which is diabetic ulcers caused by peripheral neuropathy. Diabetes Mellitus (DM) cases at Kraton Hospital, Pekalongan Regency in 2023 is 232 cases. This study aims to sensitivity of bacterial findings in isolates of acute ulcers and chronic ulcers in Diabetes Mellitus patients at Kraton Hospital, to prescribed antibiotics. The type of method used was analytical descriptive research, namely to determine and test differences in the sensitivity of bacterial findings in acute ulcer and chronic ulcer isolates in Diabetes Mellitus patients at Kraton Hospital, to prescribed antibiotics. There are differences in the results of sensitivity tests for acute ulcer samples and chronic ulcer samples. There is a difference in the sensitivity test results of acute ulcer samples and chronic ulcer samples, namely in sample 1 (acute) Staphylococcus aureus is sensitive to Ampicilin while Escherichia coli is sensitive to all antibiotics tested (Ampicilin, Meropenem, Metronidazole, and Ciprofloxacin), in sample 2 ( acute) Escherichia coli and Pseudomonas aeruginosa were sensitive to Meropenem, while in sample 3 (chronic) Proteus mirabilis was sensitive to Ampicilin.